1986
DOI: 10.1136/gut.27.6.667
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of immunoglobulin producing cells is different in normal human appendix and colon mucosa.

Abstract: SUMMARY The densities of IgG-, IgA-, IgM-and IgD-producing immunocytes were determined by paired immunofluorescence staining and morphometric analysis in the lamina propria of normal appendix specimens. Normal colon specimens were used as reference material, mostly paired from individual subjects. The density (median of cells/mm2 lamina propria area) of IgA immunocytes tended to be slightly higher in the appendix than in the colon (1259 vs 962) and the same held true for IgM cells (71 vs 55). Conversely, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…The appendix does also seem to be of central importance in the development of mucosal immune function, with a high proportion of immune cells of both T-and B-cell lineage. 42,43 An interesting epidemiologic study showed that removal of an inflamed appendix is protective for the development of UC but not of CD. 44,45 Appendectomy may reduce the exposure of goblet cell autoantigens for the immune system and hence reduce the risk of developing an immune reaction against goblet cells.…”
Section: Figurementioning
confidence: 99%
“…The appendix does also seem to be of central importance in the development of mucosal immune function, with a high proportion of immune cells of both T-and B-cell lineage. 42,43 An interesting epidemiologic study showed that removal of an inflamed appendix is protective for the development of UC but not of CD. 44,45 Appendectomy may reduce the exposure of goblet cell autoantigens for the immune system and hence reduce the risk of developing an immune reaction against goblet cells.…”
Section: Figurementioning
confidence: 99%
“…It has been found that secretory IgD cells in the peripheral blood are rare (∼3%), but make up a substantial population of the human respiratory tract mucosal B cells (17,29). In contrast to the upper respiratory tract, there are few IgD plasma cells in the digestive system mucosae, with only trace amounts of IgD in digestive fluids (30)(31)(32)(33). This indicates that IgD plasma cells are highly localized, and therefore may be related to the function of their secretory product.…”
Section: Discussionmentioning
confidence: 99%
“…This population had the advantage of containing a high frequency of sIgA' B cells (20). Moreover, the appendix has been shown to exhibit features of GALT, and this includes a dome region covered by a unique epithelium containing follicle-associated or microfold cells, that function in the uptake of gut antigens for the induction of mucosal immune responses (21).…”
Section: Discussionmentioning
confidence: 99%